2009
DOI: 10.1254/jphs.09040sc
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Method for Evaluation of Gastrocecal Transit Time by Using a Breath Test in Conscious Rats

Abstract: The aim of this study was to establish a method for evaluating gastrocecal transit time using a simple and noninvasive 13C breath-test system in conscious rats. After fasting, rats were orally administered lactose-[13C]ureide. 13CO2 level in the expired air was measured at appropriate intervals. It was confirmed that priming dose of lactose-ureide was necessary for determining gastrocecal transit time. The level of 13CO2 in the expired air increased in a lactose-[13C]ureide dose-dependent manner. The gastrocec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…We also confirmed that a priming dose of lactose-ureide is necessary in the breath testing of rats (Uchida et al, 2009a). Therefore, the first phase of each experiment involved evaluating the effect of this priming dose of lactose-ureide on gastric emptying.…”
Section: Effects Of Primed Lactose-ureide and Lactose-ureide Containesupporting
confidence: 71%
See 3 more Smart Citations
“…We also confirmed that a priming dose of lactose-ureide is necessary in the breath testing of rats (Uchida et al, 2009a). Therefore, the first phase of each experiment involved evaluating the effect of this priming dose of lactose-ureide on gastric emptying.…”
Section: Effects Of Primed Lactose-ureide and Lactose-ureide Containesupporting
confidence: 71%
“…Ruemmele et al (1997) reported that human gut tissues possess no allantoicase-like activity. In basic research, we reported that a priming dose of lactose-ureide is also needed for rats to enable the investigation of gastrocecal transit time using lactose-[ 13 C] ureide (Uchida et al, 2009a). Therefore, we evaluated at first the effects of a priming dose of lactose-ureide and the simultaneous administration of lactose-ureide instead of lactose-[ 13 C] ureide on gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, in basic research we developed a simple and non-invasive breath test system for evaluating gastric emptying and pancreatic exocrine secretion in conscious rats [6][7][8]. Recently, we also reported a non-invasive and feasible method for the evaluation of the rat gastrocecal transit time by using lactose-[ 13 C]ureide [9]. However, the drug effect affecting the gastrocecal transit time has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%